Affordances-Based Brand Relations: An Inquire on Memetic Brands on Instagram - Caliandro, Alessandro; Anselmi, Guido (Social media + society, 2021)
In this article, we argue that, in an era of platformization of culture, social media users tend to relate with brands through modalities that are more informed by platforms’ affordances (i.e., by the technical architecture of and participatory cultures thriving on social media platforms), rather than shared systems of values and meanings promulgated within brand communities or influencers’ fandoms. Our argument grounds on an analysis of 757,776 Instagram posts related to six global brands, through which we show how users create branded content by following and reproducing a memetic logic. Drawing on our empirical results and Limor Shifman’s theory of Internet memes, we introduce the notion of memetic brands. Memetic brands are collections of branded social media posts, which derive from a standard branded template that repeats from user to user with small compositional changes at every iteration and on top of which users attach expressions of their vernacular creativity. In the process, memetic brands vehiculate a hypersignification, that is, an implicit discourse on fluid and situational consumption. Through the concepts of affordances-based brand relations and memetic brands, the article contributes (from a theoretical and methodological point of view) to the emerging literature on platformization of culture.